Laboratory Evaluation of Fatigue Damage and Healing of Asphalt Mixtures - Daniel, Jo Sias; Kim, Y. Richard (Journal of materials in civil engineering, 2001)
The changes in the stiffness of two asphalt concrete mixtures due to temperature, fatigue damage growth, and healing during rest periods are evaluated using the impact resonance method. The impact resonance method is a means of determining the dynamic modulus of elasticity of a specimen nondestructively. The dynamic modulus of elasticity decreases as temperature increases and as microcrack damage growth occurs in the specimen due to fatigue. The impact resonance method also detects increases in dynamic modulus of elasticity after the application of rest periods. A gain in flexural stiffness was also observed from measurements and is attributed to closure of microcracks or healing during the rest period. The amount of healing or stiffness gain appeared to increase when specimens were subject to a higher temperature during the rest period. A qualitative study of the two asphalt mixtures showed that there is a difference between the two with respect to healing performance.